FINALITAS YESUS MENURUT KLAUSA “SESUNGGUHNYA AKULAH PINTU KE DOMBA-DOMBA ITU”: EKSEGESIS INJIL YOHANES 10:7 - Sensius Amon Karlau (Sekolah Tinggi Teologi Ekumene Jakarta., 2020)
The frequent claims made by followers of Jesus regarding His finality as the only Savior continue to be challenged by groups who speculate against such claims as do liberals and conservatives who build on subjective understanding. This has an impact on efforts to account for faith which have increasingly experienced distortion of the religiosity of faith in the past to the present. This article aims to present the finality of Jesus, as He spoke of both to groups who reject it as well as to His followers in an effort to enrich the teachings of modern Christology. The author uses qualitative methods with an exegetical approach with data collection techniques, namely reviewing the literature in order to understand the meaning of